2015
DOI: 10.1016/j.jtcvs.2014.12.058
|View full text |Cite
|
Sign up to set email alerts
|

Histologic changes associated with the use of fibrinogen- and thrombin-impregnated collagen in the prevention of pulmonary air leakage

Abstract: TachoSil provided a mechanical scaffold on which healing could proceed, followed by biodegradation over the long term. TachoSil safely repaired the pleural defects without affecting lung parenchyma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Additional methods, including the application of sealants such as collagen-coated patches, fibrin glue, and other synthetic materials, have been used to minimize air leak severity and duration [6,7]. Sealants based on a fixed combination of a collagen patch coated with human thrombin-fibrinogen sponge-like Ta-choSil ® (Takeda, Osaka, Japan) have also been used [8,9]. However, results from studies comparing TachoSil ® with classical surgical techniques have not demonstrated additional value when using the sealant if airtightness was established with conventional practices [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…Additional methods, including the application of sealants such as collagen-coated patches, fibrin glue, and other synthetic materials, have been used to minimize air leak severity and duration [6,7]. Sealants based on a fixed combination of a collagen patch coated with human thrombin-fibrinogen sponge-like Ta-choSil ® (Takeda, Osaka, Japan) have also been used [8,9]. However, results from studies comparing TachoSil ® with classical surgical techniques have not demonstrated additional value when using the sealant if airtightness was established with conventional practices [6,8].…”
Section: Introductionmentioning
confidence: 99%
“…First, the interrelationships among the different cell lines involved during the reparative process may partially explain the development of PAL in human beings when some regenerative processes fail to occur. According to the results produced by Tsubokawa and associates, 3 the mechanisms responsible for the airtight covering of the lung and the reparation of the pleural defect occur early in the healing process, before POD 7. The mesothelium migrates through the collagen scaffold to cover the outermost layer of the fleece by POD 4, and this supports the clinical observation that most air leaks resolve by this time.…”
mentioning
confidence: 99%
“…The article in this issue of the Journal by Tsubokawa and associates 3 addresses this important missing issue. Tsubokawa and associates 3 are to be congratulated for producing a very elegant experimental study that details the dynamic healing mechanisms of a pleural defect when covered by a sealant.…”
mentioning
confidence: 99%
“…Despite the effective use of surgical staplers and the "hilum first, fissure last" technique, incomplete interlobar fissures are associated with a risk of damage to visceral pleura and a subsequent probability of a prolonged air leak (1). A prolonged air leak has adverse impacts on morbidity, culminating in a lengthy hospitalization with negative effects and delayed adjuvant treatment (2).…”
mentioning
confidence: 99%